Analysis of Determining Factors for Indonesian Coal Exports to 11 Regional Comprehensive Economic Partnership (RCEP) Countries - Ardelia Nisa, Sahda; Puspitawati, Eka (Department of International Relations Universitas Pertamina, 2021)
This study aims to determine export price, real GDP, exchange rates, geographic distance, and coal reserves of export destination countries on Indonesia coal export value to 11 RCEP countries for period 2010-2019 and describe the growth of Indonesian coal export value to 11 RCEP countries for period 2010-2019. The eleven RCEP countries are China, Australia, Japan, Korea, New Zealand, Singapore, Malaysia, Thailand, Philippines, Vietnam, dan Cambodia. This study used quantitative data with panel data regression. The results of the simultaneous significance test indicate that globally the independent variables in the model significantly affect the dependent variable. These results are supported by the partial test that export price, real GDP, and exchange rates has a positive significant effect on value of Indonesia coal export, while geographic distance and coal reserves of export destination countries has a negative significant effect on Indonesia coal export value.